SOCIAL NETWORK MODELING BY USING COUPLED OCSILLATORY SYSTEMS - Uwate, Yoko; Nishio, Yoshifumi (Journal of Advanced Manufacturing Technology (JAMT), 2016)
In this study, we investigate the clustering phenomena in a social network of coupled chaotic circuits. We observe the various clustering phenomena in a social network model using coupled chaotic circuits when we change the scaling parameter of the coupling strength.